Acute maculopapular eruption in Covid‐19 patient: A case report. Issue 6 (12th July 2020) - Rossi, E.; Lasagni, C.; Trakatelli, M.; Wertzberger Rowan, S.; Magnoni, C.
Abstract: We report the case of a positive COVID‐19 patient who presented to our hospital for a maculopapular skin rash which appeared 7 days after the onset of COVID‐19 symptoms. He was 34 years old and nothing relevant was recorded at his previous anamnesis. The patient was hospitalized for 3 days and received systemic therapy with steroid, antihistamines, tocilizumab, and hydroxicloroquine. On the third day of the hospitalization the cutaneous rash had almost completely disappeared.